Associations between physical health conditions and posttraumatic stress disorder according to age. (1st February 2021) - Sommer, Jordana L.; Reynolds, Kristin; El-Gabalawy, Renée; Pietrzak, Robert H.; Mackenzie, Corey S.; Ceccarelli, Laura; Mota, Natalie; Sareen, Jitender
Abstract: Objectives: Posttraumatic stress disorder (PTSD) is associated with various physical health conditions. However, it is unclear whether the relationship between PTSD and physical health conditions differs according to age. This study aims to examine the associations between PTSD and physical health conditions across four adult age categories. Methods: We analyzed data from the 2012 to 2013 National Epidemiologic Survey on Alcohol and Related Conditions ( N  = 36, 309). The Alcohol Use Disorder and Associated Disabilities Interview Schedule-5 assessed past-year DSM-5 PTSD. Multiple regression analyses examined associations between PTSD (reference = no PTSD) with number and type of physical health conditions in each age category (18–34: "younger adults, " 35–49: "middle-aged adults, " 50–64: "young-old adults, " 65+: "older adults"). Results: The prevalence of nearly all physical health conditions increased according to age, whereas the prevalence of PTSD tended to decrease with age. After adjustment, PTSD was associated with a greater number of physical health conditions among all age categories ( b range: 0.62–1.29). Regardless of age category, PTSD was associated with increased odds of cardiovascular and musculoskeletal conditions (AOR range: 1.54–2.34). PTSD was also associated with increased odds of gastrointestinal, hepatobiliary, endocrine/metabolic, respiratory, neurologic conditions, cancer, sleep disorders, and anemia among select age categories (AOR range: 1.70–3.31). For most physical health conditions, the largest effect sizes emerged for younger and middle-aged adults. Conclusions: PTSD is associated with many physical health conditions across the age spectrum, particularly among younger and middle-aged adults. Results may inform targeted screening and intervention strategies to mitigate risk of physical health conditions among adults with PTSD.